2011
DOI: 10.2967/jnumed.110.078725
|View full text |Cite
|
Sign up to set email alerts
|

A β-Camera Integrated with a Microfluidic Chip for Radioassays Based on Real-Time Imaging of Glycolysis in Small Cell Populations

Abstract: An integrated β-camera and microfluidic chip was developed that is capable of quantitative imaging of glycolysis radioassays using 18F-FDG in small cell populations down to a single cell. This paper demonstrates that the integrated system enables digital control and quantitative measurements of glycolysis in B-RafV600E–mutated melanoma cell lines in response to specific B-Raf inhibition. Methods The β-camera uses a position-sensitive avalanche photodiode to detect charged particle–emitting probes within a mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 34 publications
1
46
0
Order By: Relevance
“…Furthermore, the uptake values obtained with CIMR are indirect estimations compared with the previous in-culture microfluidic radioassay using a loading and flushing protocol (11). Adapting the infusion profile of CIMR with flushing of the tracer allows the pure event density of cells to be measured, and the uptake values we calculated were consistent with the continuously measured CIMR uptake (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Furthermore, the uptake values obtained with CIMR are indirect estimations compared with the previous in-culture microfluidic radioassay using a loading and flushing protocol (11). Adapting the infusion profile of CIMR with flushing of the tracer allows the pure event density of cells to be measured, and the uptake values we calculated were consistent with the continuously measured CIMR uptake (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Nevertheless, the significant correlations between the relative uptake ratios (0.5/5 and 2.5/5 mM) for the two types of measurements demonstrated the consistency of the relative relations between them. As many studies investigate the relative differences under certain interventions, the systematic bias between CIMR and conventional uptake may not change the results if all the investigations are performed using in-culture measurement (11). Smaller variations were achieved with in-culture measurement using CIMR than with conventional uptake experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few methods have demonstrated the ability to visualize the uptake of radionuclide probes with single-cell resolution. One of these methods uses a bsensitive avalanche photodiode to measure radionuclide uptake in small groups of cells, cultured in 16 microfluidic chambers (8). An experiment showed that the avalanche photodiode could measure signal from a single cell in the chamber.…”
mentioning
confidence: 99%